Melting behaviour of binary mixtures of palm mid fraction and rice bran oil - Saadah Mastura Saidin,; Nazaruddin Ramli, (Universiti Kebangsaan Malaysia, 2010)
The melting and crystallization profile of cocoa butter substitute (CBS) formulation consisting of oil blends between palm mid fraction (PMF) and rice bran oil (RBO) were measured through solid fat content using pulsed Nuclear Magnetic Resonance (pNMR) Bruker Minispe. The isothermal melting and crystallization behaviour were determined via Differential Scanning Calorimeter (DSC). The formulations were developed through binary mixture of palm mid fraction and rice bran oil with different ratios created using Mixture Design, Design Expert version 6.0. Selected formulations had been studied for compositional modification through immobilized lipase catalyzed by interesterification using Novozyme® 435. Three selected parameters such as temperature (40-60 oC), catalyst concentration (2-10%) and time (4-48 h) at 200 rpm orbital shaking with 14 formulations acquired by applying D-Optimal experimental design had been applied. The results showed that blends of 75% palm mid fraction with 25% rice bran oil and its 14 enzymatic interesterification (EIE) yields have the potential to perform the desired behaviour as the crystals are completely melt at 32.48 - 38.28 oC. However, the yields of formulation with EIE condition of 60 oC, 10% lipase and 48 h incubation time (labeled N) formed stable β crystals during tempering as it had melting peak at 34.19 oC which was closer to melting point of cocoa butter required in tempering to form V crystals (~34 oC), that assured best chocolate appearance and texture.